2009
DOI: 10.1115/1.2987240
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Hot-Streak Simulators for Turbine Testing

Abstract: The importance of understanding the impact of hot-streaks, and temperature distortion in general, on the high pressure turbine is widely appreciated, although it is still generally the case that turbines are designed for uniform inlet temperature—often the predicted peak gas temperature. This is because there is an insufficiency of reliable experimental data both from operating combustors and from rotating turbine experiments in which a combustor representative inlet temperature profile has accurately been sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…"Inlet profile generators" are then used to approximate the combustor exit flow supplied to the turbine rig. State-of-the-art work along these lines include, most recently, the work of Colban and co-workers [3,4], Barringer and co-workers [5,6], Povey and Qureshi [7,8], and Simone et al [9]. These past approaches have led to an improved understanding of the sensitivity of the turbine to the various inflow parameters separately, e.g., OTDF level.…”
Section: Introductionmentioning
confidence: 95%
“…"Inlet profile generators" are then used to approximate the combustor exit flow supplied to the turbine rig. State-of-the-art work along these lines include, most recently, the work of Colban and co-workers [3,4], Barringer and co-workers [5,6], Povey and Qureshi [7,8], and Simone et al [9]. These past approaches have led to an improved understanding of the sensitivity of the turbine to the various inflow parameters separately, e.g., OTDF level.…”
Section: Introductionmentioning
confidence: 95%
“…Povey and Qureshi [1] provided a comprehensive review of facilities which were adapted for use in hot-streak (ITD) studies. Among the earlier facilities discussed (The Warm Core Turbine Test Facility at the NASA Lewis Research Center [2], The Large Scale Rotating Rig at the United Technologies Research Center [3], and The Rotating Blow-Down Facility at MIT [4,5]) experimental studies focused on the introduction of ITD and the investigation of ITD migration through the UP stage.…”
Section: Introductionmentioning
confidence: 99%
“…There is a big variety in the temperature ratios used in combustors depending on the design field of application. Compared to the study of Povey et al [13], this ratio is in the range observed in modem annular combustors used in aircraft engines. The peak temperature was approximately positioned at midspan and midpassage between the two stator blades.…”
Section: Experimental Methodsmentioning
confidence: 61%